THE INFLUENCE OF LEADERSHIP ON THE MANAGEMENT OF YAYASAN BAKTI ANAK SHALEH INSAN TELADAN - Putri Purnama Sari; Dedi Dedi (Journal of Public Administration, 2022)
This study aims to analyze the influence of the Leadership of the Head of Foundation on the Management of the Bakti Anak Shaleh Insan Teladan Foundation (YABASIT). This research was cunducted at the YABASIT. Using a sample of 21 volunteers (employees) who work at the YABASIT, data was collected using a questionnaire and interviews (interviews). Based on the results of the regression calculation, it can be concluded that the coefficient value of variable influence of leadership is 4,051. The regression coefficient X of 0,883 states that for each additional value of the Leadership indicator, the Foundation Management indicator increases by 0,883. Based on the value of tcount = 9,088 > ttable = 2,093, so H0 is rejected and it can be conclude that there is a significant influencce of the Leadership of the Foundation on Foundation Management at the YABASIT.